Relationship of Early Breastfeeding and Sunbhating Initiation to Physiological Jaundice Decreased on Neonates in MombyKids Jombang: Hubungan Inisiasi Menyusu Dini dan Sunbhating Terhadap Penurunan Ikterus Fisiologis Pada Neonatus Di Mombykids Jombang - Fatmawati, Zeny; Barir, Baroroh; Kristianingrum, Dhita Yuniar (Jurnal Kebidanan Midwiferia, 2022)
Newborns are prone to physiologic icterus characterized by yellow mucosa and baby's skin due to deposition of heme catabolism, bilirubin. Various prevention can be done to prevent jaundice of newborns to become hyperblirubinemia. The purpose of this study was to analyze the relationship between the reduction in physiologic jaundice in neonates. Analytic observational research design, samples of all babies born in Mombykids Jombang in November 2019 -March 2020 were 60 babies, purposive sampling technique, instruments used were observational sheets and fisher's exact test was analyzed. Early breastfeeding initiation done for one hour y 75%, sunbhating done for 15-30 in the morning minutes as much as 80%, decreased physiological signs of jaundice as much as 80%, there is a relationship between early breastfeeding initiation, sunbhating with decreased physiological signs of jaundice during neonates with fisher's exact test p = 0,000 α = 0.05. Educating mothers and breastfeeding on the importance of prevention of jaundice during neonates about the benefits of giving early breastfeeding initiation, namely providing the opportunity for newborns to immediately get breast milk in the form of collustrum and do neonatal drying in the morning sun for 15- 30 minutes.